INTEGRASI EKONOMI ISLAM DAN CIRCULAR ECONOMY UNTUK PEMBANGUNAN BERKELANJUTAN - ROIFAH, TRI NADHIROTUR ROIFAH (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study examines the integration of the Circular Economy (CE) and Islamic Economics (IE) to formulate a more coherent model of sustainable development. The analysis focuses on the conceptual relationship between CE and IE, the potential adaptation of zakat, waqf, and Sharia-compliant financing as mechanisms for implementing circular practices, and the key challenges that emerge in aligning the two paradigms. The findings indicate strong alignment between CE’s regenerative and resource-efficient principles and the ethical foundations of IE, particularly trustworthiness (amānah), distributive justice, and the objectives of maqāṣid al-sharīʿah. This convergence provides a robust normative and operational basis for developing a regenerative development framework. The study further reveals that zakat supports community-based circular initiatives, productive waqf facilitates long-term sustainable investments, and Sharia financing promotes innovation in circular business models. Nevertheless, CE–IE integration faces several obstacles, including philosophical divergences, variations in maqāṣid interpretation, limited normative literature on modern material-loop mechanisms, and regulatory as well as institutional capacity gaps. Overall, the study highlights the strategic potential of CE–IE integration in advancing a holistic sustainable development paradigm that unites material efficiency with social justice and long-term well-being.